The Use of Different Endorser Types in Advertising: A Content Analysis of Magazine Advertisements. Issue 3 (27th May 2019) - Schimmelpfennig, Christian
ABSTRACT: Most of the literature assumes that endorsements, particularly by celebrities, are a frequently used advertising strategy. However, no study has yet investigated the use of the different endorser types identified by academic literature. This study seeks to close this research gap by analyzing German print advertisements. It finds that endorsement strategy in general is used much less than academic literature assumes, and that the relative significance of the different endorser types is incongruent to expectations. Moreover, the data suggest that, contrary to the literature's assumptions, credibility is not the most important underlying construct for endorsement advertisements, the endorser type used is frequently determined by the product category that is being advertised, and campaigns based on authenticity and similarity are gaining considerable importance in advertising practice.